Solubilization of C60 using ultrasound and amphiphilic block copolymers in acidic aqueous solutions. Issue 5 (4th May 2019) - Wang, Yanxia; He, Ting; Yang, Heng; Gao, Ming; Chai, Zhihua
Abstract: Fullerene (C60 ), the third carbon allotrope, has shown great potential in photoelectric materials and drug delivery. However, the low solubility of C60 in polar solvents, especially in water, is the major limiting factor for further applications. The use of ultrasound and amphiphilic block copolymers, poly(ethylene glycol)- block -poly(4-vinylpyridine) (PEG- b -P4VP), helped to disperse C60 in acidic aqueous solutions. As characterized by dynamic light scattering, transmission electron microscopy, and UV-visible spectroscopy, the C60 colloids had a core-shell structure with C60 aggregated in the micellar cores. The photosensitized generation of singlet oxygen using C60 -bound polymer micelle was confirmed by the iodide method. More importantly, C60 and metalloporphyrin complexes could be synthesized by the self-assembly between PEG- b -P4VP/C60 micelle and metalloporphyrin. The stability of metalloporphyrin increased in the presence of the PEG- b -P4VP/C60 micelle. This study provides a method for the solubilization of C60 with many potential applications in biomedicals and photovoltaics.